Education Fostering Moral Integrity In Vocational Education: The Influence Of Islamic Religious Instruction In The Global Era - Dalimunthe, Amsal Qori; Sundowo, Edi; Sinulingga, Neng Nurcahyati; Neliwati, Neliwati (At-Tarbiyat, 2024)
This study analyzes the role of Islamic Religious Education (PAI) in building students' moral resilience at SMK Swasta Tunas Pelita Kota Binjai in the era of globalization. Using a descriptive qualitative approach and interactive analysis, this research involved in-depth interviews, observations, and documentation from teachers, students, and school stakeholders. The research findings show that curriculum integration planning and teacher training contribute positively to students' moral resilience. Effective PAI implementation is done through methods such as discovery learning, group discussions, and extracurricular activities, with teachers acting as facilitators and motivators. Contextual strategies, review of religious texts, and integration with other sciences also strengthen the implementation of religious values in students' lives. Support from the principal and PAI teachers through evolutionary and revolutionary approaches also play an important role in achieving learning objectives. This study highlights the importance of active learning strategies, curriculum integration, and school environment support to shape students' moral resilience, providing practical implications for PAI curriculum development in the era of globalization.